Improvement of Service Tasks, Position Obligations of Municipal Employees in Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This comprehensive paper explores the progressive stages of development witnessed by local self-governing bodies, highlighting the complex evolution of community structures. The article moves through historical milestones, legislative frameworks and stages of change, offering readers a nuanced view of the changing landscape of local government. Basically, this article serves as a "road map" that guides self-governing bodies and community workers in the direction of development. Its rich content combines historical context with contemporary issues, making it a key resource for anyone seeking to understand the complex model of local governance.